Prooxidant activity of phenolic stabilizers in polyolefins during accelerated photooxidation. (August 2019) - Šlouf, Miroslav; Michálková, Danuše; Gajdošová, Veronika; Dybal, Jiří; Pilař, Jan
Abstract: Polymer plaques made of high density polyethylene (HDPE) and of two types of cycloolefin copolymer (COC) differing in glass transition temperature, were stabilized with 0.2 or 1.0 wt % of natural (α-tocopherol) or synthetic (Irganox®1010) phenolic stabilizer or hindered amine stabilizer (Tinuvin®770) and aged using accelerated weathering technique (WOM). The efficiency of the phenolic stabilizers was compared among themselves and with well-established Tinuvin®770. Concentration profiles of radicals generated inside polymer plaques during WOM exposure were determined by ESRI, profiles of oxidation products and crystallinity inside the HDPE plaques were determined by IR microspectroscopy, oxidation products in COC copolymers were identified using ATR, the changes of local mechanical properties of the polymer plaques were characterized using microindentation hardness testing, and their morphology was studied by light and/or scanning electron microscopy. All the techniques evidenced high stability of neat COC against photooxidation processes, whereas neat HDPE exhibited fast photooxidation of the surface layers. Tinuvin®770 was found to provide long term protection to both HDPE and COC against photodegradation. In contrast, the same polymers stabilized with the natural phenolic antioxidant α-tocopherol (the most active component of vitamin E) or synthetic phenolic antioxidant Irganox®1010 exhibited an increase in the surface oxidation in comparison with the neat polymers during WOM exposure, proving prooxidant activity of phenolic stabilizers during WOM exposure in all polymers studied. The prooxidant activity α-tocopherol was stronger in comparison with Irganox®1010. We conclude that neither of the two phenolic stabilizers was able to provide long term protection of the investigated polymers against photooxidation . Highlights: Accelerated weathering of HDPE and COC polymers stabilized with phenolic stabilizer. Prooxidation activity of 1% of α‑tocopherol or Irganox® 1010 during photooxidation. Limited prooxidation activity at lower concentration of stabilizers (0.2 wt %). The stabilizers do not protect the polymers subjected to photooxidation.